(x + 2)² + (2x – 1)² = 5x (5x + 1)
Soluções para a tarefa
Respondido por
2
Resposta:
- 20x² -5x + 5 = 0
Explicação passo a passo:
(x + 2)² + (2x - 1)² = 5x (5x + 1)
(x² + 2 . x . 2 + 2²) + ((2x)² - 2 . 2x . 1 + 1²) = 25x² + 5x
(x² + 4x + 4) + (4x² - 4x + 1) = 25x² + 5x
x² + 4x + 4 + 4x² - 4x + 1 - 25x² - 5x = 0
- 20x² + 4x + 4 - 4x + 1 - 5x = 0
- 20x² -5x + 4 + 1 = 0
- 20x² -5x + 5 = 0
Perguntas interessantes
Português,
7 meses atrás
Geografia,
7 meses atrás
Português,
7 meses atrás
Matemática,
8 meses atrás
Inglês,
8 meses atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás